Industrial policies and small enterprise development : the case of disadvantaged and special sectors - Bissember, Enid E. (CARICOM Secretariat GeorgetownGY, 1994)
Attempts to identify the trends in small enterprise development throughout the region. Examines efforts by policy-makers to assist the sector to grow and achieve its true potential.